The relation between leisure activities and glycemic levels from deaf adults - Inacia Sátiro Xavier de França; Jamilly da Silva Aragão; Alexsandro Silva Coura; Caroline Evelin Nascimento Kluczynik Vieira; Joedson Felipe da Silva; Giovanna Karinny Pereira Cruz (Rev Rene)
The aim has been to check the association among leisure activities and glycemic levels from deaf adults. Transversal study made with 36 deaf adults in an Audiocomunicação school, making use of a semi-structured questionnaire. Chi-square, Fisher and Contingency Coefficient tests were made. Unfed capillary glycemic average showed up close to values considered usual, however, there are participants with risky glycemic level. Participants with altered glycemic levels totalized 11,1%. We checked association among deaf glycemic people having leisure activities, go shopping (p=0,034) and visiting relatives (p=0,012). Leisure activities may have influence over glycemic levels of deaf people, and nurses are supposed to consider stimuli and orientation of leisure activities in nurse processes, as a potential intervention to promote health of those people, and prevent implications caused by altered glycemic levels.